Nutritional Composition of (Australian Sweet Lupin) Natto and Tempeh: Effect of Source and Fermentation Time - Wickramasinghe, Niranjani Priyadarshani (Curtin University, 2017)
This PhD thesis describes the generation of lupin tempeh and natto from two sources of lupin; whole seed and dehulled seed. In this thesis I discuss the changes that occur in nutritional composition and functional attributes of lupin tempeh and natto as a function of fermentation time. I also present data of the in vitro bio- availability of nutrients from these sources.